(3TQM eUGHjM GdSfIs - (3Rjf GdYQH Ydj Hf YHO Gddg CMeOs; (3CHh eMeO GdMSjf Hf eSYhO Hf eMeO GdaQGA GdHZhj GdTGaYj eMjj GdSfI,J (B516 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdHjhY s
(3BNQgG (B:s
(3hYdi GdNjQ hGdUdGM fbWY GdcdGe , QGLjf ef Gddg GdadGM hGddg MSHfG hfYe Gdhcjd Je GdLRA GdKGfi hgh BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI MQjVI ecJHI YeQ Hf CMeO GdYehOi GdYGeI s
Keywords: (3GdMOjK h GdeUWdMs